IMPLEMENTASI KETERBUKAAN INFORMASI PUBLIK DALAM PENGELOLAAN KEUANGAN DESA (STUDI DI DESA BURAN KECAMATAN TASIKMADU KABUPATEN KARANGANYAR) - F., Adriana Grahani; Kurniawan, Rony (Res Publica: Jurnal Hukum Kebijakan Publik, 2017)
This study aims to identify and analyze the urgency and implementation of public information disclosure in village financial management in Desa Buran Kecamatan Tasikmadu Kabupaten Karanganyar. This research is an empirical law study. The nature of descriptive research. Data collection techniques used were interviews and literature study. The data analysis technique used is quantitative. Based on the results of research and discussion, the conclusions are: First, the urgency of public information disclosure in the management of village finances in Desa Buran is to realize the implementation of democratic village governance by mainstreaming transparency in order to ensure certainty of village financial management process. Second, the implementation of public information disclosure in village financial management in Desa Buran is not optimal, because the Village Government still uses very limited media in conveying information related to village financial management